2017
DOI: 10.1007/s00432-017-2341-6
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol esters in seed oil of Jatropha curcas L. (saboodam in Thai) and their association with cancer prevention: from the initial investigation to the present topics

Abstract: PurposeIn 1988, we first reported the complete chemical structure of a new type of phorbol ester, abbreviated to DHPB, found in seed oil of Jatropha curcas L. (Saboodam in Thai) and its tumor-promoting activity on mouse skin. Although this seed oil contains toxic phorbol ester, it was planned to use it as a feasible renewable oil and the extracted seed cake as fertilizer. This utilization value opened a new science of Jatropha curcas.MethodsThe main experimental results are cited from our publications, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…On the other hand, Hirota et al (2017) reported the identification of DHP as the fundamental structural core which is derived from 12-deoxy-16-hydroxy-phorbol-4 - [12 ,14 -butadienyl]-6 -[16 ,18 ,20 -nonatrienyl + were also reported in J. curcas seeds (Wink et al, 2000). Even more so, Haas, Sterk & Mittelbach (2002) reported the identification of diterpenes named Jatropha factors C 2 to C 6 through ESI-MS m/z 711 [M+H] + and of DHP (m/z of 365 [M+H] + ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Hirota et al (2017) reported the identification of DHP as the fundamental structural core which is derived from 12-deoxy-16-hydroxy-phorbol-4 - [12 ,14 -butadienyl]-6 -[16 ,18 ,20 -nonatrienyl + were also reported in J. curcas seeds (Wink et al, 2000). Even more so, Haas, Sterk & Mittelbach (2002) reported the identification of diterpenes named Jatropha factors C 2 to C 6 through ESI-MS m/z 711 [M+H] + and of DHP (m/z of 365 [M+H] + ).…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, Brazil and India, non-toxic varieties of this species have been identified with very low or non-detectable levels of phorbol esters (PEs) in seeds ( Laviola et al, 2010 ; Martínez-Herrera, Chel-Guerrero & Martínez-Ayala, 2004 ; Kumar, Anand & Reddy, 2011 ). PEs are known as Jatropha factors because each one of them has the same nucleus diterpene moiety, namely, 12-deoxy-16-hydroxy-phorbol (DHP) which is coupled to unstables intramolecular diterpenes (named C 1 –C 6 factors) ( Hirota et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Hirota et al (2017) reported the identification of DHP as the fundamental structural core which is derived from 12-deoxy-16-hydroxy-phorbol-4'-[12',14'-butadienyl]-6'- [16',18',20'-nonatrienyl (Wink et al, 2000). Even more so, Haas, Sterk & Mittelbach, (2002) reported the identification of diterpenes named Jatropha factors C 2 to C 6 through ESI-MS m/z 711 [M+H] + and of DHP (m/z of 365 [M+H] + ).…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, Brazil and India, it have been identified non-toxic varieties of this species with very low or non-detectable levels of phorbol esters (PEs) in seeds (Laviola et al, 2010;Martínez-Herrera, Chel-Guerrero & Martínez-Ayala, 2004;Kumar, Anand & Reddy, 2011). PEs are known as Jatropha factors because each one of them has the same nucleus diterpene moiety, namely, 12deoxy-16-hydroxy-phorbol (DHP) which is coupled to unstables intramolecular diterpenes (named C 1 -C 6 factors) (Hirota et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they can induce acute toxic effects in animals and insets and cause skin irritant and promote tumors in human beings (Becker and Makkar, 1998;Devappa et al, 2012;Katole et al, 2011;Li et al, 2010;Rug and Ruppel, 2000). In contrast, recent studies revealed phorbol esters can exhibit antimicrobial and antitumor activities when applied at low concentrations (Devappa et al, 2013b;Fujiki et al, 2017). The diverse bioactivities of phorbol esters are not only dependent on dosage effects but also associated with varied structures among phorbol esters and their derivates.…”
Section: Introductionmentioning
confidence: 99%